INDUSTRY OF THE REPUBLIC OF UZBEKISTAN. SMALL BUSINESS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This abstract encapsulates the dynamic landscape of small businesses within Uzbekistan's industrial sector, highlighting the pivotal role they play in economic development and diversification. Uzbekistan's government has implemented robust reforms to foster entrepreneurship, streamline administrative procedures, and enhance access to finance for small enterprises. Key initiatives include promoting innovation and technology adoption, supporting sectoral diversification, and facilitating international partnerships to integrate small businesses into global value chains. Challenges such as infrastructure limitations and skills shortages persist but are being addressed through capacity-building programs and market access support. Looking ahead, Uzbekistan aims to empower small businesses through digital transformation, sustainable practices, and collaborative partnerships, positioning them as engines of inclusive and sustainable economic growth. This abstract provides insights into Uzbekistan's commitment to nurturing a vibrant small business ecosystem within its industrial landscape.